Contagion and Information Frictions in Emerging Markets: The Role of Joint Signals - Besart Avdiu; Tobias Gruhle (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We show that information frictions can explain financial contagion without correlated fundamentals and explain why emerging markets are more susceptible to contagion. Costly information may cause investors to group country signals, because such imprecise signals are cheaper. These joint signals then cause asset prices to comove, which can be observed as contagion. Due to lower demand for country-specific information and lower risk weighted returns, it is likelier that investors group signals of emerging markets, thereby making them more prone to contagion. We find empirical evidence for our predictions using a novel data set on the number of joint news articles and exploit exogenous variation in news due to terrorism.
Keywords: D8; F30; G11; 330; Financial Crises; Emerging Markets; Contagion; Information Choice; News